Comparison of dexmedetomidine and buprenorphine as an adjuvant to bupivacaine during spinal anaesthesia for tibial interlocking nailing surgeries - S., Amitha; R., Pradeep (International Journal of Advances in Medicine, 2017)
Background: Buprenorphine is being used as an adjuvant to local anaesthetic for spinal anaesthesia since long. Dexmedetomidine is a new drug which has got alpha 2 agonistic property, and is being tried for spinal anesthesia along with bupivacaine in recent times. Settings and Design: This study was conducted in a prospective, randomized, controlled and double-blind manner. The study included ninety American Society of Anaesthesiologists class I and II patients undergoing tibial interlocking nailing surgeries under spinal anaesthesia. Methods: The patients were randomly divided into three groups (n=30 each) by closed envelope technique. Patients in group 1 received 15 mg of 0.5% hyperbaric bupivacaine, group 2 received 15 mg of 0.5% hyperbaric bupivacaine with 30μg of buprenorphine, and group 3 received 15 mg of 0.5% hyperbaric bupivacaine with 5μg dexmedetomidine for spinal anesthesia. The duration of motor and sensory blockade and any adverse events were recorded. Data were analysed using Chi-square test or Fisher’s exact test for categorical data and analysis of variance for continuous data. A value of P<0.05 was considered as statistically significant. Results: In our study the subjects in group 3 (dexmedetomidine) group had significantly longer period of motor blockade (240±20min) and sensory blockade (180±22.2min) compared to other groups, which is statistically significant (P=0.0001 and P= 0.006 respectively). The time to first request of analgesic in the post-operative period was also longer (240±30.2min) in dexmedetomidine group when compared with other groups (P=0.0001). There were no untoward complications (hypotension, sedation) in any groups. Conclusions: We concluded that dexmedetomidine (5μg) with bupivacaine for spinal anesthesia gives significantly longer duration of sensory and motor blockade, than buprenorphine (30μg) with bupivacaine for spinal anaesthesia.